KARAKTERISTIK SOSIODEMOGRAFI, KERAGAMAN KONSUMSI PANGAN SERTA TINGKAT KECUKUPAN ENERGI DAN PROTEIN TERHADAP KEJADIAN KEKURANGAN ENERGI KRONIS PADA REMAJA PUTRI - Adhi, Kadek Tresna; Andani, Ni Komang Irna Ayu (ARCHIVE OF COMMUNITY HEALTH, 2024)
Chronic Energy Deficiency or CED is a condition that occurs in adolescent girl or eligible woman due to a long-lasting lack of energy and protein intake marked by the size of the upper arm circumference <23.5 cm. The prevalence of CED in Indonesia has fluctuated from 2007-2018. CED can have short-term and long-term health impacts on adolescent girl. Sociodemographic factors and nutritional intake are two factors causes CED in adolescents. This study aims to prove sociodemographic characteristics, diversity of food consumption, energy and protein adequacy levels as risk factors for CED in adolescent girls. This study used a case control design. The data were obtained from a nutrition survey in all high schools in Bangli Regency. The selection of control samples using a matching system. Data analysis using univariate and bivariate methods. Bivariable analysis showed that sociodemographic characteristics were number of family members (p=0.001; OR= 0,23, 95% CI= 0,09-0,56) were significantly associated with the incidence of CED in adolescents girl. Monitoring nutritional status and providing nutrition education to adolescents can be done to prevent the occurrence of CED.  Keywords: CED, Dietary, Energy, Protein, Adolescent.